Freezing as an intervention to reduce the numbers of campylobacters isolated from chicken livers. (28th May 2013) - Harrison, D.; Corry, J.E.L.; Tchórzewska, M.A.; Morris, V.K.; Hutchison, M.L.
Abstract: The aims of this study were (i) to determine the prevalence and numbers of campylobacters in 63 samples of raw livers purchased at retail across the UK and (ii) to investigate whether the freezing of chicken livers contaminated with Campylobacter was a reliable method for decontamination. Chicken livers naturally contaminated with campylobacters were subjected to freezing at −15 and −25°C for one day and 7 days. Numbers of campylobacters on the livers were determined immediately before and after a 24‐h or 7‐days freeze treatment and daily during 3 days post‐thaw refrigerated storage. Freezing for 24 h at −25°C can reduce numbers of Campylobacter by up to 2 log10  CFU g −1 . Freezing the livers for 24 h at −25°C, thawing overnight in a fridge set to 4°C and refreezing for another 24 h at −25°C reduced the numbers of campylobacters by up to three logs. Reduction in the numbers of campylobacters was significantly greater following a second freeze treatment compared with a single freeze treatment. Significance and Impact of the Study: Freezing chicken livers can reduce, but not eliminate, campylobacters. If poultry processors were to freeze livers destined for human consumption as part of routine processing, there is a potential for a reduction in campylobacteriosis associated with the consumption of imperfectly cooked chicken livers and derivatives, such as pâté. Abstract : Significance and Impact of the Study: Freezing chicken livers can reduce, but not eliminate, campylobacters. If poultry processors were to freeze livers destined for human consumption as part of routine processing, there is a potential for a reduction in campylobacteriosis associated with the consumption of imperfectly cooked chicken livers and derivatives, such as pâté.